SUMOylation of zebrafish transcription factor Zbtb21 affects its transcription activity - Zhou Fang; Yun Deng; Haihong Wang; Jun Zhou (PeerJ, 2024)
Background Post-translational modification by Small Ubiquitin-like MOdifier (SUMO) is an important mechanism to regulate protein activity, protein stability, and localization of substrates. Zbtb21 is a zinc finger and BTB (Broad-complex, Tram-track and Bric à brac) domain-containing transcription factor. Bioinformatic prediction suggests several putative SUMOylated sites in Zbtb21 protein. Methods Two evolutionarily conserved lysine residues in Zbtb21 protein were mutated alone or in combination to disrupt the binding with SUMO molecules. Western blot and co-immunoprecipitation analyses were performed to detect the SUMOylation state of wild type and mutant Zbtb21 proteins, respectively. Luciferase reporter assays were conducted to evaluate their transcription activities. Meanwhile, immunofluorescence staining was carried out to show their sub-nuclear localizations. Finally, co-immunoprecipitation was performed to detect the interaction between Zbtb21 and its partners. Results Phylogenetically conserved lysines 419 and 845 of zebrafish Zbtb21 protein can be conjugated with SUMO molecules. SUMOylation does not affect the subcellular localization and protein stability of Zbtb21, as well as the interaction with Zbtb14 or Zbtb21. Nevertheless, luciferase reporter assays revealed that Zbtb21 is a dual-function transcription factor which exerts activation or repression effect on different promoters, and SUMOylation can modulate the transcriptional activity of Zbtb21 in regulating downstream target genes. Hence, Zbtb21 is identified as a novel substrate of SUMOylation, which would be important for its function. Conclusions Zebrafish Zbtb21 protein can be SUMOylated on lysines 419 and 845, which is evolutionary conserved. SUMOylation affects the dual role of Zbtb21 on transcription.